Why some VO members do not benefit from RDP intervention: a panel study of ten selected cases - Banu, Dilruba (BRAC, 2019)
The Rural Development Programme (RDP) of BRAC provides a comprehensive service to poor women incorporating awareness building, training, savings generation, credit disbursement and income generating activities. The Second Impact Assessment Study of BRAC's RDP revealed that economic condition of a few member households did not improve. Furthermore, their asset holding decreased over three years. This study aimed to identify the factors that inhibited success of those members. The study also highlighted the reasons for their long time involvement in BRAC even though their household economy was declining. The analysis used a combination of 10 case studies and data from sample survey. Life-cycle factors were pronounced in the sample households for their declining situation. In a few cases old age of main income earner was a barrier of their regular earning. Childbearing responsibilities also prevented young members to be involved directly in income generating activities. Economic factors caused downward mobility of the sample households as well. The value of their living houses ranged between Tk 350- 19,600. Nine members lived in their own houses built on their own lands. The other one built house on the land of her brother-in-law. None of the sample members had borrowed housing loan from BRAC. The mean value of the productive assets such as cow, poultry, rickshaw, rickshaw van, etc. was Tk 4,706. - Inconsistent income of the household heads due to involvement in low return activities was a barrier to their economic improvement. Their income was also affected by seasonality. Nine households had more than one income earner, but the second earner was mainly a female. Eight VO members were involved with small economic activities. Level of their income was very low as they could not manage to work on a large scale. None of them used the BRAC loan in their own economic activity and consequently, they lost their control over both loan and profit acquiring from it. Five members received training from BRAC on skill development but they failed to initiate new enterprises at small scale due to lack of entrepreneurship skill. Nine members received loans from BRAC ranging from Tk 2,000- 15,000. Due to family crises improper utilization of loan money caused declining economic condition of some sample households. Some of the members were not happy with the amount of BRAC loan. They mentioned that the amount of BRAC loan was too little to start a new enterprise. Four members joined other NGOs and two of them received loans from them. Crises factors acted as the main impediment to their economic improvement. Over the previous three years, each of the sample households faced some family contingencies, which directly affected the economic condition of their households. Crises mainly included the death or illness of principal income earner of the household and loss of production modes like cow, rickshaw van, power tiller, etc. The households made distress sales of assets to cope with crises. Due to lack of leadership skill, the members were unable to link them with the network of their VOs. Access to loan was the main reason for continuing their membership in BRAC. Most of the members mentioned improvement of their bargaining power within the household as they brought a big amount of cash from BRAC. Members claimed ownership on some small assets like poultry, goat and jewelry bought from their own income. In a few cases they claimed control on these as well. They were able to take part in decision making on some familial aspects and their mobility increased. To some extent their legal and political awareness has been increased. But their social status has not improved significantly. Belonging to same economic stratum, members have similar perceptions of their social environment and they adhere to similar beliefs. Regarding their empowerment it seemed that BRAC could not build awareness and augment motivation effectively among them. Finally, members improved their position in their immediate households through their access to loan, although they could not manage to improve their economic condition considerably. Case study revealed that six members could resist their declining economic condition by increasing ratio of income earner to dependent members and to find out employment with a regular income flow. Three of the sample members had already left BRAC for some unanticipated reasons. Prevention of inactivity and dropout of members required a reduction of their vulnerability during period of their crises.